Is contextual cueing more than the guidance of visual-spatial attention? - Schankin, Andrea; Hagemann, Dirk; Schubö, Anna (Biological psychology, 2011)
When search displays are repeatedly presented, participants become faster in finding the target (contextual cueing, CC). It has been debated whether a more liberal response criterion might contribute to CC. In the current experiment, participants had to search through target-absent and target-present trials to compute d-prime as the measurement of sensitivity and beta as the measurement of response bias. Results showed that participants’ sensitivity was not affected by the repetition of search displays. Although repeated displays led to both faster RTs and a more liberal response criterion, these effects were uncorrelated. In the event-related potential, RT effects were reflected by a late positive activity, which reflects response-related processes, but not by differences in the N2pc as electrophysiological correlate of focused attention. These results indicate that a more liberal response criterion is not the cause for CC effects in RTs but that other response-related processes might still contribute to the effect.
Gesehen am 10.10.2022